2016
DOI: 10.1177/0363546516657525
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Risk Factors Associated With Noncontact Anterior Cruciate Ligament Graft Rupture

Abstract: The geometric risk factors for ACL graft rupture are different for males and females. For females, a decreased femoral intercondylar notch width and a decreased height of the posterior medial meniscus were risk factors for ACL graft rupture that have also been found to be risk factors for first-time injury. There were no risk factors in common between ACL graft injury and first-time ACL injury for males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 62 publications
6
79
0
1
Order By: Relevance
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau .…”
Section: Discussionsupporting
confidence: 51%
“…Prior work has shown that increased posterior-inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL 18,19 and ACL graft injury, 24 and the increased lateral compartment JOURNAL OF ORTHOPAEDIC RESEARCH ® APRIL 2020…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included articles had the following designs: five retrospective cohort studies [5,8,[20][21][22], six prospective cohort studies [2,[23][24][25][26][27], four case series studies [28,-31], five controlled laboratory studies [32-36], three retrospective case control studies [13,15,37], and two prospective case control studies [16,38]. The risk factors catalogued in these studies are grouped into factors the patient can alter against factors the patient has no control over (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While prevention of primary ACL injury has been heavily studied, it is of interest to study the factors associated with recurrent and subsequent contralateral ACL reconstructions. A review of the literature reveals numerous reports of associated modifiable and nonmodifiable factors [2][3][5][6][7][8][12][13][14][15][16][17][18][19]], but no comprehensive evaluation. Awareness of modifiable and non-modifiable factors allows for intervention to decrease rates of recurring ACL rupture.…”
Section: Introductionmentioning
confidence: 99%